2004
DOI: 10.1038/sj.sc.3101615
|View full text |Cite
|
Sign up to set email alerts
|

Stepping-like movements in humans with complete spinal cord injury induced by epidural stimulation of the lumbar cord: electromyographic study of compound muscle action potentials

Abstract: Study design: It has been previously demonstrated that sustained nonpatterned electric stimulation of the posterior lumbar spinal cord from the epidural space can induce stepping-like movements in subjects with chronic, complete spinal cord injury. In the present paper, we explore physiologically related components of electromyographic (EMG) recordings during the induced stepping-like activity. Objectives: To examine mechanisms underlying the stepping-like movements activated by electrical epidural stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
250
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(283 citation statements)
references
References 41 publications
10
250
1
1
Order By: Relevance
“…There is a very consistent difference between the evoked potentials in flexor and extensor motor pools in both rats and humans (Gerasimenko et al, 2001;Minassian et al, 2004). For example, monosynaptic responses are prominent in extensor motor pools, whereas the flexor motor pools are activated predominantly polysynaptically in response to ES.…”
Section: Which Axons and Neurons Are Being Activated By Es?mentioning
confidence: 94%
“…There is a very consistent difference between the evoked potentials in flexor and extensor motor pools in both rats and humans (Gerasimenko et al, 2001;Minassian et al, 2004). For example, monosynaptic responses are prominent in extensor motor pools, whereas the flexor motor pools are activated predominantly polysynaptically in response to ES.…”
Section: Which Axons and Neurons Are Being Activated By Es?mentioning
confidence: 94%
“…The evoked potentials forming the late response differed in the TA and MG: the progression of the onset delays during consecutive stimuli was evident only in MG. Similarly, long-latency responses were more prominent in flexors than extensors during stimulation-induced stepping in humans (Gerasimenko et al, 2001Minassian et al, 2004) and during stimulation-and quipazine-facilitated stepping in spinal rats . The timing of recovery of weight-bearing stepping highlights the functional significance of the phase-dependent modulation of the late response in TA and MG. As suggested previously , the presence and amplitude of the late, but not middle, response appear to be related to the degree of locomotor recovery after transection.…”
Section: What Are the Middle And Late Responses Evoked By Epidural Stmentioning
confidence: 97%
“…9 On the other hand, Gerasimenko 10 reported that such epidural stimulation of the rat spinal cord elicited early, intermediate and late responses in several extensor and flexor muscles in the hind limb. Further, they showed that those early-evoked responses are, in fact, direct stimulation of the spinal cord and not the dorsal roots.…”
Section: Introductionmentioning
confidence: 99%